Effect of Potassium Chloride and Sodium Bicarbonate Supplementation on Thermotolerance of Broilers Exposed to Heat Stress - Naseem, M.T.; Naseem, Shamoon; Younus, M.; Ch., Zafar Iqbal; Ghafoor, Aamir; Aslam, Asim; Akhter, S. (International Journal of Poultry Science, 2005)
A total of 100-day-old broiler chicken were randomly divided into five groups and kept under elevated temperature (95-98.6oF) to observe the effect of potassium chloride and sodium bicarbonate on the weight gain, feed conversion ratio (FCR), serum potassium and serum bicarbonate level. Thermostress lead to significant in decrease (P< 0.05) weight gain, serum potassium and serum bicarbonate level, while FCR was increased. During heat stress, KCl and NaHCO3 at levels of 1.5% and 0.5% respectively, improved weight gain, and FCR and significantly increased (P< 0.05) serum potassium and bicarbonate level. The results showed that combination of KCl and NaHCO3 supplementation alleviated the negative effects of heat stress in broilers.